Progress of Hematopoietic Stem Cell Transplantation and Radiotherapy in the Treatment of Extranodal NK/T Cell Lymphoma - Terro, Khodr; Sharrouf, Layal; El Cheikh, Jean (Frontiers in Oncology, 2022)
Extranodal Natural Killer/T-cell lymphoma (ENKTL) is an extremely rare type of lymphoma which is highly lethal. It mainly affects the midline area unfolding as a necrotic granulomatous and extremely disfiguring lesion. There are two subtypes of (NKTL); the most common one is nasal which appears in the nasal cavity. While the other rarer subtype, appears in sites like the skin, testis, gastrointestinal tract, salivary glands and muscle. However, there is no single unified consensus yet as to what is the standardized treatment for ENKTL. Radiotherapy alone treatment, has been considered as a first-line therapy for localized ENKL, which later on was found to be insufficient for improving survival rates. Thus, the combination of chemotherapy and radiotherapy has been recommended as a therapeutic modality for localized ENKL. Several combination modalities of radiotherapy and chemotherapy have been advised in clinical practice including concurrent, sequential and sandwich chemo radiotherapy. For the best treatment outcome, only patients with localized nasal ENKTL and low risk of treatment failure are eligible for radiotherapy. Both radiotherapy and hematopoietic stem cell transplantation (HSCT) have been used as treatment modalities in ENKTL patients. Upfront HSCT was performed for ENKTL, but it was associated with a very poor prognosis even for the limited-stage disease. The end result was a unified consensus that consolidative HSCT is not necessary in patients with newly diagnosed localized ENKL who achieved complete response after treatment with any of the modern chemo radiotherapy regimens. Hence, HSCT is solely advised for advanced and relapsed NKTL.